Kewenagan Pemerintah Desa dalam Pemberdayaan Petani di Desa Gunung, Kecamatan Kota Komba, Kabupaten Manggarai Timur - Maria Derici Rofdilu Sadung; Yohanes G. Tuba Helan; Yohanes Tuan (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The magnitude of potential and knowledge needs in agriculture requires community empowerment, especially farmers. Community empowerment is an activity or way in an effort to make the community more empowered or able to overcome problems in themselves and their environment. Gunung Village, Kota Komba District, East Manggarai Regency until now has not received maximum yields due to the influence of community knowledge about how to farm properly and correctly, therefore the community needs knowledge in agriculture, it is required to empower the community, especially farmers as regulated in Law of the Republic of Indonesia Number 19 of 2013 concerning the Protection and Empowerment of Farmers Article 1 CHAPTER 1. This makes the basis for research to find out the government's ability to empower farmers in Mountain Village, Kota Komba District, East Manggarai Regency. The type of research used is empirical juridical research or called field research, which examines applicable legal provisions and what happens in reality in society.The results show: (1) That in the implementation of farmer empowerment in Gunung Village, the village government collaborates with the agriculture office to socialize education and training, counseling and mentoring as well as the development of a marketing system for agricultural products to the village community to improve agriculture in the village, (2) supporting factors in empowering farmers in Gunung Village include the Budget, leadership and Power of the Village Head, The Government has a good relationship with the community, while the inhibiting factors in empowering farmers in Gunung Village include community attitudes, and low skills of farmers.